A critical role for Vibrio parahaemolyticus LPS to mediate evasion of host immune response during infection - Jananee Jaishankar; Hyojik Yang; Ian P. O’Keefe; Brandon M. Tenaglia; Lisa N. Kinch; Robert K. Ernst; Kim Orth (Proceedings of the National Academy of Sciences, 2025)
Vibrio parahaemolyticus ( V. para ), a Gram-negative halophilic bacterium, is the leading cause of seafood-borne gastroenteritis. While the cytotoxic and enterotoxic capabilities of this bacterium have been previously investigated, the strategies it employs to circumvent innate immune detection by the host remain poorly understood. Bacterial lipopolysaccharide (LPS) serves as the major pathogen-associated molecular pattern that triggers host inflammatory responses, and its lipid A structure contributes to the degree of innate immune system activation. We sought to define the structure of the lipid A component of LPS in V. para and probe its role in host innate immunity. Free living V. para synthesizes a predominantly hepta-acylated lipid A structure, while also producing a minor subset of hexa-acylated lipid A. This altered acylated lipid A elicits a weakened TLR4 immune response as compared to Escherichia coli , allowing V. para entry and replication inside host cells. Deletion of the V. para lipid A biosynthesis enzyme lpxM (VP0213) leads to a mutant strain with altered lipid A secondary acylation, enhanced immune response, and impaired replication within epithelial cells. This study provides evidence that the unique LPS structure synthesized by V. para plays a crucial role in evading host innate immunity, facilitating the bacterium’s survival and replication within host cells.